Research progress on petroleum coke for mercury removal from coal-fired flue gas. (1st February 2022) - Sun, Zhiqiang; Ma, Anjun; Zhao, Shilin; Luo, Hui; Xie, Xingyu; Liao, Yiren; Liang, Xin
Highlights: Mercury removal from coal-fired flue gas by PC-based adsorbent is reviewed. Physicochemical and demercuration properties of modified PC are discussed. Mechanochemically modified PC is a promising mercury removal adsorbent. Optimal modification parameters for each PC-based adsorbent need further study. Abstract: Mercury pollution from coal combustion has attracted widespread attention. Petroleum coke (PC), a by-product from petrochemical industry, is a potential substance to replace activated carbon mercury removal adsorbent. Most of the published articles on PC-based mercury removal adsorbent are reviewed in this work. It shows raw PC has little mercury removal ability (5%). Pyrolysis can increase mercury removal ability of PC with limited improvement effect (below 60%). KOH activation benefits for pore structure development but results in sulfur removal. SO2 activation improve surface pore structure and sulfur content of the PC, which can realize Hg 0 capture rate higher than 90%. The mercury species on the used SO2 impregnated PC are mainly HgSblack and HgSred . The mechanochemical liquid bromine modified PC can achieve very high mercury removal efficiency of above 98%. However, the effects of pyrolysis, SO2 activation, and mechanochemical modification parameters on the surface physical–chemical properties especially sulfur forms of PC, as well as the modification mechanism and mercury removal mechanism need to be further studied. Mechanochemically modified PC is a promising mercury removal adsorbent. This work hopes to provide guidance for the development of high-performance PC-based mercury removal adsorbents and its industrial application.